Construction of a police physical evaluation model and standards based on law enforcement ability - Feng, Yuliang; Liu, Yang; Wang, Dexin (Frontiers in Physiology, 2024)
Purpose: In the context of police practical combat with the essence of coercion and confrontation, police physical fitness training guided by practical combat is increasingly valued. The objective of this study was to establish a police physical evaluation model and standards based on law enforcement ability. Methods: Using literature analysis, expert interviews, Delphi method, field testing, and mathematical statistics, the test results of 301 frontline law enforcement police officers from the Shanghai Public Security Bureau were used as sample data. Factor analysis was conducted on the selected indicators to determine the final indicator system for police physical fitness. The percentile method was used to develop evaluation standards, and frequency statistics and chi-squared tests were used to calculate the effectiveness and accuracy of the evaluation standards. Results: The research results revealed that the police physical fitness evaluation model based on law enforcement ability is Y = 0.115 × 30 s of trigger pulling according to the gun + 0.105 × 30 s of straight punching sandbags + 0.095 × 30 s of wrestling the dummy + 0.062 × push-ups + 0.115 × 50-m run + 0.095 × 10 m × 4 round trips + 0.116 × standing long jump + 0.090 × 2,000-m run + 0.089 × 30 s of hitting sandbags using a short baton + 0.118 × 30 s of poking sandbags using the long baton. The evaluation criteria were divided into single-item and comprehensive evaluation criteria. Conclusion: A practical police physical fitness evaluation model can effectively evaluate the level of police physical fitness development, and the evaluation standards can provide an effective basis for a practical police physical fitness evaluation.